Manajemen Diversity dan Kesetaraan dalam Lembaga Pendidikan Islam: Suatu Analisis Realitas Sosial - Riyadi, Ivan (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
This article is written based on consideration of the reality of students as a diversity and equality community that is unique to discuss, often also occurs in Islamic educational institutions in diversity that can be solved by diversity management and equality that have a spirit of togetherness and vision of unity. To get a complete picture in this article, a qualitative approach to the design of literature research is used. The results show that diversity management and equality can be a solution to create peace in the school's scope of diversity. The relationship of educational institutions to the community is an effort that can be felt in creating harmony among ethnic groups.